Numerical parameters and quality indicators in a Medical Emergency Department Kennzahlen und qualitätsindikatoren einer medizinischen notaufnahme - Dormann, Harald; Diesch, Katharina; Ganslandt, Thomas; Hahn, Eckhart Georg (Deutsches Ärzteblatt, 2010)
Background: Despite calls for improved quality and efficiency in medical emergency departments, there exist hardly any quality indicators, and no methods of calculating efficiency have been published to date. The present study illustrates a means of presenting numerical parameters of a medical emergency department and of identifying potential quality indicators. Methods: Over a period of 12 months, all patient contacts of the medical emergency department in the University hospital of Erlangen were analyzed with respect to patient flow, diagnoses, and treatment units. The diagnostic agreement (DA) parameter was calculated from a systematic comparison of admitting and discharge diagnoses, and diagnostic efficiency (DE) was defined and calculated as the quotient of DA x100 divided by the length of stay in the emergency department. Results: Among the 6683 patients treated, 64.6% underwent further in-hospital care. The diagnostic spectrum of the outpatients differed markedly from that of the inpatients. Patients with diseases of the heart, gastrointestinal tract, and lungs were usually admitted to the hospital for further treatment. Patient contacts had a characteristic circadian and weekly rhythmic pattern. For the overall patient collective, the DA was 71%. The mean length of stay in the emergency department was 116 minutes, and the DE was therefore 0.61/min. The DA was highest (92%) among patients with atrial flutter or fibrillation, while the DE was highest (0.85/min) among patients with acute myocardial infarction. 14% of the patients required further treatment in intensive care. Conclusion: Numerical parameters and quality indicators for a hospital emergency department can be presented in transparent fashion. DA and DE can be used as parameters for diagnosis-related and intradepartmental quality assessment. © 2010 Deutsches Ärzteblatt, Deutscher Ärzte-Verlag GmbH.
CRIS-Team Scopus Importer:2021-11-16